2002
DOI: 10.1177/154405910208101206
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases have a Role in Palatogenesis

Abstract: Mammalian palatogenesis depends on palatal shelf elevation, medial edge epithelium (MEE) breakdown, and mesenchyme flow. These all require matrix remodeling, which is controlled in part by the family of matrix metalloproteinases (MMPs). We used an organ culture system to examine the effect of a general MMP inhibitor (BB3103) on mouse palatogenesis. Palates cultured in 20 micro M BB3103 contained no active MMP-2, and only one palate fused from a sample size of 15. In this single palate, MMP-3 was present at hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
1
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 15 publications
1
51
1
6
Order By: Relevance
“…Blocking basal lamina degradation by inhibiting MMP activity, however, had no effect on cell death. These results contrast with two recent reports (Blavier et al, 2001;Brown et al, 2002) showing partial or no MEE degeneration in the presence of the same MMP inhibitor used here. In our experiments, we demonstrated [with high reproducibility even at the low inhibitor dose (10 µM)] that the basal lamina was intact.…”
Section: Discussioncontrasting
confidence: 99%
“…Blocking basal lamina degradation by inhibiting MMP activity, however, had no effect on cell death. These results contrast with two recent reports (Blavier et al, 2001;Brown et al, 2002) showing partial or no MEE degeneration in the presence of the same MMP inhibitor used here. In our experiments, we demonstrated [with high reproducibility even at the low inhibitor dose (10 µM)] that the basal lamina was intact.…”
Section: Discussioncontrasting
confidence: 99%
“…In MMP9 analysis, we noted differences for maxillary tooth agenesis but not for mandible tooth agenesis. One possible reason for the difference between the arches may be that MMPs have a role in palatogenesis, and disruption of its activity can result in cleft palate (30). In some instances, oral clefts and tooth agenesis may share the same genetic background (2,31).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of palatal MEE cells, the cells seem to develop greater matrix-dependency for survival and become sensitive to anoikis during EMT, because EMT is always associated with integrin-mediated cell scattering on the substrates, defined by the loss of intercellular junctions and acquisition of cell motility (Hay, 1995;Boyer et al, 2000). Recently, Blavier et al (2001) and Brown et al (2002) showed that the activity of MMPs (matrix metalloproteinases) is indispensable for disappearance of the MEE seam and disruption of its basement membrane during palatal fusion, and that at least MT1-MMP, MMP-13, and MMP-3 are expressed in the MEE at the time of midline seam disruption. These MMPs are known to digest not only type IV collagen and laminins of basement membrane but also a variety of other extracellular matrix components, such as fibronectin, type I and III collagens, and proteoglycans (Werb, 1997;Seiki, 2003).…”
Section: G D E H F I Jmentioning
confidence: 99%
“…Although palate organ cultures enable various experiments which are impossible in utero, they sometimes produce conflicting results. Palate culture methods reported thus far can be largely divided into the static culture method using a CO 2 incubator (Pourtois, 1966(Pourtois, , 1968Smiley and Koch, 1971, 1972, 1975Dixon and Ferguson, 1992;Griffith and Hay, 1992;Martínez-Álvarez et al, 2000;Cuervo et al, 2002;Cuervo and Covarrubias, 2004) and the suspension culture method with rolling bottles (Shiota et al, 1990;Brown et al, 2002). In those cultures, some fundamental questions remain such as: (1) In order from the left, oral and medial views of the single shelf explants, and the cell morphology of the medial edge and oral and nasal epithelia, respectively.…”
Section: Introductionmentioning
confidence: 99%